Micro and Macro Elements Content of Mushroom Substrate Fortified with Selected Naturally Fermented Solutions - Galon, Francis (Journal of Interdisciplinary Perspectives, 2025)
This study evaluated the effects of organic fortifications—fermented fruit juice (FFJ), indigenous microorganisms (IMO), and fish amino acids (FAA)—on the yield and nutrient composition of mushrooms. Four treatments were applied: T0 (control), T1 (FFJ), T2 (IMO), and T3 (FAA), with yield data collected across multiple replications. Results showed that T1 produced the highest yield (539.6g), followed by T2 (535.2g), T3 (528.8g), and T0 (518.8g). However, analysis of variance (ANOVA) indicated no statistically significant differences among treatments (p > 0.05), suggesting that organic fortifications did not substantially enhance yield. Nutrient analysis revealed treatment-dependent variations in macronutrient and micronutrient content. T0 had the highest nitrogen (N) and copper (Cu) levels, while T2 exhibited the highest potassium (K) and zinc (Zn) content. Notably, molybdenum (Mo) was only detected in T1. These findings suggest that organic fortifications may influence nutrient availability in mushrooms, although their overall effects were limited. Despite slight improvements in yield and nutrient composition, organic fortifications did not produce statistically significant benefits. Further research is recommended to optimize application methods, explore synergistic effects with other organic amendments, and assess economic viability for large-scale mushroom cultivation.